Strategising Future 'banks': Hypothetical Model - Paul, Justin (Ushus Journal of Business Management, 2005)
The banking sector is going through a phase of consolidation and restructuring in India. 'Survival of the Fittest' has become a reality in the case of public sector commercial banks, with the opening up of new branches in all districts by new generation banks such as ICICI and HDFC and the Customer Relationship Management (CRM) practices implemented by private and foreign banks.